Mobile Platform for Car Service - Abdelhamed, M. N.; Shchenyatsky, A. V. (Вестник ИжГТУ имени М.Т. Калашникова, 2021)
The analysis of the use of drives of mobile and transport robots is given. Various options for design solutions are considered, including the main selected drive of a mobile platform with four Omni-wheels, ensuring maximum mobility and maneuverability. Masses and ground clearance of vehicles of various classes are estimated to determine the overall dimensions of the mobile platform in terms of height and carrying capacity. It has been established that the necessary elements of a mobile platform are universal mounting plates and trailed equipment. The control systems of two variants have been developed. The first is automatic, for an autonomous mobile platform, and the second is for remote control. Control systems include 3 microcontrollers, 5 drivers, 6 motors, 4 sensors. The position of the mobile platform can be controlled by the operator remotely using a mobile application. Power supply of the MP is carried out from its own battery, from the car network or an external network. An algorithm for the operation of the control system for different versions is proposed. 3D models of the mobile platform and suspension unit models have been developed. Calculations of the lifting mechanism of the MP are given. The layout of the nodes of the mobile platform is presented.